2006
DOI: 10.1007/bf02984659
|View full text |Cite
|
Sign up to set email alerts
|

Transient ischemic dilation ratio (TID) correlates with HbA1C in patients with diabetes type 2 with proven myocardial ischemia according to exercise myocardial SPECT

Abstract: Diabetes and its long- term unsatisfactory compensation can be one of the factors which affect left ventricular transient ischemic dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many MPI indices are associated with myocardial perfusion abnormalities and coronary artery disease. SRLVV ratio is higher in persons with diabetes [27][28][29][30], particularly those who later develop cardiac events. Subendocardial ischemia or stress-induced stunning [31] may cause TID, which is an independent predictor of future cardiac events [8,31].…”
Section: Discussionmentioning
confidence: 95%
“…Many MPI indices are associated with myocardial perfusion abnormalities and coronary artery disease. SRLVV ratio is higher in persons with diabetes [27][28][29][30], particularly those who later develop cardiac events. Subendocardial ischemia or stress-induced stunning [31] may cause TID, which is an independent predictor of future cardiac events [8,31].…”
Section: Discussionmentioning
confidence: 95%
“…13 These findings raise important questions about the pathophysiology and the diagnostic and prognostic value of TID in the presence of diabetes mellitus. Recently, Petretta et al 14 found that TID provides incremental diagnostic information over standard myocardial perfusion analysis for the identification of severe and extensive CAD in patients with diabetes mellitus.…”
Section: Clinical Perspective On P 915mentioning
confidence: 99%
“…Thus, the findings suggested exercise-induced systolic (as well as possibly diastolic) left ventricular dysfunction, and along with autonomic neuropathy, the presence of diabetic cardiomyopathy. Transient ischemic left ventricular dilatation (TID) shown by a stress myocardial perfusion SPECT scan is a marker of the presence of severe coronary artery disease [6,7]. The patient had a normal TID value as well as negative exercise testing result.…”
Section: Case Reportmentioning
confidence: 99%